Manganês e biorregulador em soja RR2 manejada com Glyphosate - Cantú, Carine (2018)
The cultivation of RR (Roundup Ready®) soybean has increased over the past few years and, as a result, changes regarding weed management have been evidenced, with emphasis on the intensification of glyphosate use. However, research results report that in some cases, the herbicide has caused phytotoxic effects on the soybean crop. Thus, the objective of this study was to evaluate the behavior of manganese and of the bioregulator in reversing possible damages caused by glyphosate herbicide in RR soybean. Two experiments were carried out during the 2016/17 crop in Palotina, PR. In the first experiment, the experimental design was a randomized block design in 5 x 4 factorial arrangement with 5 doses of glyphosate (0; 720; 1440; 2160 and 2880 g. e.a. ha-1) and 4 doses of manganese (0; 92,4; 184,8 and 369,6 g ha-1). Glyphosate and manganese were applied together via foliar at V4 stage. The variables evaluated were: chlorophyll index, plant height, insertion height of the first pod, number of pods, 1.000 grain mass and yield. The results showed the glyphosate effect in reducing the number of pods per plant due to the increase of herbicide doses. Regarding the foliar application of Mn, there was an increase in the number of pods per plant and consequently in yield. It was observed that an increase in Mn doses up to 261,64 g Mn ha-1 increased grain yield. In the second experiment, the experimental design was a randomized block design, in 5 x 4 factorial arrangement with 5 doses of glyphosate (0; 720; 1440; 2160 and 2880 g. e.a. ha-1) and 4 management (manganese application; bioregulator application; association of both; no application). The glyphosate, manganese and bioregulator were applied together via foliar at V4 stage. The evaluated variables were phytotoxicity symptoms and others described in the first experiment. Under the environmental conditions of this experiment and for the evaluated genotype, the application of glyphosate in the studied formulation, regardless of the dose used, presented very mild phytotoxicity symptoms in the RR soybean plants and the management applied (bioregulator and Mn) was not effective as phytotoxicant reversers. Therefore, phytotoxicity did not interfere in the evaluated agronomic characteristics and production components. Despite the results verified in these experiments, in general, the cultivar under study showed to be highly tolerant to glyphosate, considering that the herbicide had no effect on the vegetative and reproductive development of soybean plants to the point of reducing grain yield. It is highlighted the need for additional studies in order to evaluate other genotypes, locations and years/crop and to reassess the potential of using manganese and bioregulator in the management with glyphosate in RR2 soybean.